2016
DOI: 10.1002/jcb.25464
|View full text |Cite
|
Sign up to set email alerts
|

Foxc1 Expression in Early Osteogenic Differentiation Is Regulated by BMP4‐SMAD Activity

Abstract: FOXC1 is an important regulator of the initial steps in intramembranous and endochondral ossification processes. As BMP signalling is a key initiator of these processes, we sought to determine whether Foxc1 expression is regulated by such signalling factors. BMP4 treatment of C2C12 cells resulted in an induction in Foxc1 mRNA levels. Chromatin immunoprecipitation assays demonstrated that SMAD proteins interacted with the mouse Foxc1 promoter approximately 300 bp upstream of the transcription start site. This C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Moreover, interleukin-8 (IL-8) induces FOXC1 expression through activation of phosphoinositide 3-kinase signaling 40, suggesting that tumor inflammation is an induction condition for FOXC1 expression. Besides, FOXC1 expression is regulated by BMP4 in early osteogenic differentiation 41. In the present study, we show that hypoxia induces FOXC1 expression in the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, interleukin-8 (IL-8) induces FOXC1 expression through activation of phosphoinositide 3-kinase signaling 40, suggesting that tumor inflammation is an induction condition for FOXC1 expression. Besides, FOXC1 expression is regulated by BMP4 in early osteogenic differentiation 41. In the present study, we show that hypoxia induces FOXC1 expression in the tumor microenvironment.…”
Section: Discussionsupporting
confidence: 62%
“…whereas non-differentiated cells generated ATP through oxidative phosphorylation (34). however animals harboring deficits in any one of these genes exhibited significant defects in bone development, formation, or mineralization (42,66,93). Sodium fluoride (NaF) is an osteoanabolic that increases bone mass but the newly formed bone lacks normal structure and strength (10,86,99).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research showed that Foxc1 expression was differentially regulated by BMP signalling at different stages of osteoblast differentiation [Hopkins et al, 2016] . Foxc1 expression is induced by BMP4 in C2C12 cells and is required for BMP4-induced osteoblast differentiation of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Primary micromass cultures from Foxc1 -/fail to induce chondrogenic nodules in response to BMP2 treatment [Kume et al, 1998] and Foxc1 function is required for activation of BMP-responsive genes in the mouse calvarium [Rice et al, 2003] . We have previously demonstrated that Foxc1 is a target for BMP induced gene expression during early stages of osteoblast differentiation of mesenchymal progenitor cells [Hopkins et al, 2016] . Foxc1 mRNA levels increased in BMP4-treated C2C12 cells through the direct binding of SMAD factors to the Foxc1 regulatory region.…”
Section: Introductionmentioning
confidence: 99%